Diversity of the dinoflagellate genus Tripos Bory 1823 (Dinophyceae) in the Western coastal waters of Tonkin Gulf, Vietnam - Pham, Tien Tai; Chu, Van Thuoc; Nguyen, Thi Minh Huyen; Duong, Thanh Nghi; Do, Thi Xuyen (Vietnam Journal of Marine Science and Technology, 2024)
Tripos is a genus of marine dinoflagellates in the family Ceratiaceae, the order Gonyaulacales (Dinophyceae). The genus Tripos has been studied in the western coastal waters of Tonkin Gulf, including 6 coastal sampling stations (Tra Co, Cua Luc, Do Son, Ba Lat, Sam Son, Cua Lo) and 2 offshore stations (Co To, Bach Long Vi) in four surveys conducted in March, June, August and November 2022. A total of 21 species belonging to the genus Tripos were initially identified in the study area. The number of species of this genus is lower in the estuarine area and higher in the offshore. The species occurred at all sampling stations, including Tripos furca, T. fusus, T. muelleri, T. trichoceros and T. breve, in which T. furca and T. fusus were the most common species. Species were common including Tripos candelabrus, T. ehrenbergii, T. gravidus, T. minutus, T. extensus and T. longipes. The species diversity in the dry season (March and November) was higher than in the rainy season (June and August). Cell density of the Tripos species varies spatially and temporally in the study area. The variation in Tripos density was related to the sampling stations, tide, sampling time, and water environment factors such as temperature, salinity, DO and pH.